A Multiperspective Approach to Self-Injurious Behavior, Bullying, and Student Mental Health: A conceptual research - Zaenudin, Zaenudin; Sukiastini, I Gusti Ayu Ngurah Kade; Faozan, Ahmad (Lembaga Penelitian dan Pemberdayaan Masyarakat, 2023)
Challenges in the education sector in Indonesia are not limited to numerical skills, literacy, and life skills alone but have expanded to encompass the low quality of students' attitudes and behaviors. These behaviors are reflected in self-harm actions, bullying, and can have negative impacts on students' mental health. The aim of the research is to provide a basis for the development of holistic intervention strategies based on a multiperspective approach to address self-harm behaviors, bullying, and mental health issues among students. A multiperspective approach allows for the integration of various perspectives in analyzing this complex phenomenon. This paper will delve deeply into these three issues. First, self-harm behaviors will be explained in various forms, including self-harm and addiction. Analysis is conducted involving psychological, social, and neurobiological perspectives to understand the causes and impacts of self-harm behaviors on students. Second, bullying as a social phenomenon is also analyzed in depth using a multiperspective approach. Individual, environmental, and cultural factors influencing bullying are explored through psychological, sociological, and educational perspectives. Finally, students' mental health becomes another focus of this paper. By utilizing a multiperspective approach, the author seeks to identify factors contributing to mental health issues among students. The analysis involves psychological dimensions, school environment, and social support. Overall, the study of a multiperspective approach is expected to provide deep insights into the complexity of the issues under examination. This holistic analysis is expected to serve as a solid basis for the development of policies, interventions, and better approaches in responding to and preventing self-harm behaviors, bullying, and mental health issues among students.